2019
DOI: 10.1002/jctb.6224
|View full text |Cite
|
Sign up to set email alerts
|

Laccases as versatile enzymes: from industrial uses to novel applications

Abstract: The application of enzymes offers an enormous potential in the improvement of existing industrial procedures and in the establishment of new processes for obtaining high-added value products. Enzymes provide cleaner and more efficient industrial processes and contribute to the sustainability concept. In this sense, laccases are very versatile biocatalysts currently used in food, textile and pulp and paper sectors among others. During the last years, scientific efforts have been diverted to the exploitation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 140 publications
(163 reference statements)
0
51
0
1
Order By: Relevance
“…Historically, the most studied enzymes in bioremediation are bacterial mono- or di-oxygenases, reductases, dehalogenases, cytochrome P450 monooxygenases, enzymes involved in lignin metabolism (such as laccases and lignin and manganese peroxidases), and bacterial phosphotriesterases [ 3 ]. From an environmental point of view, the use of enzymes instead of chemicals or microorganisms undoubtedly presents some advantages [ 4 , 5 ]. Laccases (EC 1.10.3.2, benzenediol-oxygen oxidoreductase) are either mono- or multimeric copper-containing oxidases that catalyze the reduction of oxygen to water accompanied by the oxidation of phenolic and non-phenolic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the most studied enzymes in bioremediation are bacterial mono- or di-oxygenases, reductases, dehalogenases, cytochrome P450 monooxygenases, enzymes involved in lignin metabolism (such as laccases and lignin and manganese peroxidases), and bacterial phosphotriesterases [ 3 ]. From an environmental point of view, the use of enzymes instead of chemicals or microorganisms undoubtedly presents some advantages [ 4 , 5 ]. Laccases (EC 1.10.3.2, benzenediol-oxygen oxidoreductase) are either mono- or multimeric copper-containing oxidases that catalyze the reduction of oxygen to water accompanied by the oxidation of phenolic and non-phenolic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Laccase has a great potential for integrating biotechnological processes in various industries, such as lignocellulosic biorefinery (including in the traditional pulp and paper industry), chemical, biomedical, and pharmaceutical industries. [ 92a , 92c ] Despite this, information on the current use of laccase for valorizing lignins on industrial scale is not easily found, likely due to the confidentiality that protects such processing conditions. On the other hand, some practical and technical aspects available in the literature published on laboratory‐scale experiments help to identify the challenges and opportunities regarding the current industrial use of laccases.…”
Section: Patented Applicationsmentioning
confidence: 99%
“…Attachment of such clusters to the cell surface could prove momentous, as it would provide a universal and innocuous approach for non-genetic therapeutic cell engineering 32,33 but also detoxification of xenotoxins by encapsulating enzymes within the inner compartment. Following along this line, we encapsulated laccase as an extensively studied enzyme with multiple applications 34,35 within the clustered polymersomes and demonstrated the catalytic potential of the clusters to prevent internalization of harmful compounds inducing apoptosis. In contrast to rigid DNA-linked nanoparticles and assemblies that offer limited bioactivity after endocytosis, we reveal that both the deformability of the polymersome's membrane and the lateral diffusion of the polymer chains within the membrane contribute to their surprising stability and determine the clusters' destiny in biologically relevant environments.…”
Section: Introductionmentioning
confidence: 99%